The Attractions of Marine Tourism Objects in Bireuen Regency Aceh Province (Case Study of Laut Jangka And Kuala Raja Beach Tourism Attractions) - Ruhdini, Dewi; Rahmi Novalita, Rahmi Novalita; Iqbal, Muhammad (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to identification the attractions of marine tourism objects. This research was conducted at the Laut Jangka tourist attraction and the Kuala Raja tourist attraction, Bireuen Regency. The research method used is descriptive analysis by conducting an inventory of data and tourism approaches. Primary data inventory was conducted through direct observation of the condition of the objek wisata bahari. Secondary data obtained through literature study of similar research in journals, maps and other sources. This stage is carried out by interviews, and field observations. The research results show that along the coast of Bireuen Regency there are various marine tourism objects managed by the community such as; Laut Jangka beach tourist attraction, Kuala Raja beach tourist attraction, Peuneulet Baroh beach tourist attraction, Reuleng Manyang beach tourist attraction, Calok beach tourist attraction, Laot Lapang beach tourist attraction, Ujong Blang beach tourist attraction, Blang Kiju beach tourist attraction, Pangah beach tourist attraction, and beach tourist attraction Kambuek. Identification of tourist attractions around the coast are; sunset, color of sand, swimming, fishing, catching fish using trawlers, motorbike, outbound.